HUBUNGAN ANTARA KONSEP DIRI DAN POLA ASUH ORANG TUA DENGAN KONFORMITAS SANTRI - Awaludin Mufti Efendi (Jurnal Penelitian Humaniora, 2013)
This research aims to identify the relationship between self concept and parent nurturing pattern and santri (Islamic boarding school students) conformity. Self concept is a picture owned by somebody about him or herself which formed by experiences gained from individual interaction to the environment. Whereas the parent nurturing pattern is the way parent used in treating, communicating, making discipline, monitoring and supporting children. Whereas conformity is called as a change in behavior or belief as a result of social pressure either imaginary or real. The sample of this research is 170 santris of Modern Boarding School of Imam Syuhodo Muhammadiyah Blimbing Branch Sukoharjo. The data collection technique is conducted by using questionnaire consisting of three scales, they are self concept, parent nurture pattern and conformity scale. From the data analysis, it indicates that there is significant relationship between self concept and parent nurturing pattern altogether to the santri conformity.